ANALISIS MOLEKULER PIRAMIDA GEN XA PADA PROGENI PADI VARIETAS CIHERANG DAN INPARI 13 - ., Fatimah; Prasetiyono, Joko; Priyatno, Tri Puji; Yunus, Muhammad; Suhartini, Tintin; Ridwan, Iman; Baroya, Mushlihatun (Perhimpunan Biologi Indonesia, 2015)
Bacterial leaf blight (BLB) is a major disease in Indonesian lowland rice.This research was undertaken to pyramid three BLB resistant genes xa5, Xa7 and Xa21 and one background BLB resistant gene Xa4 into Ciherang and Inpari 13 varieties. The donor parent Code (Xa4+Xa7) was crossed with Angke (Xa4+xa5) while Ciherang and Inpari 13 were crossed with IRBB21 (Xa21). Progenies were selected using marker assisted selection and yield component observation. Foreground selection was conducted using SSR and STS markers linked with the targeted genes in the F1 and DCF1 population. Individuals with triple positives Xa genes were screened for the presence of Xa4 gene as the background. Selected heterozygote plants in F1 Code x Angke, F1 Ciherang x IRBB21 and F1 Inpari 13 x IRBB21 were used to develop DCF1 population. Molecular analysis on DCF1 population through alleles of three BLB resistant genes xa5, Xa7 and Xa21 and one background BLB resistant gene Xa4 resulted 8 (2,6%) in DCF1 Ciherang and 13 (3,5%) in DCF1 Inpari 13. Yield component characters on F1 Code x Angke resulted significant in number of panicle. F1 Ciherang x IRBB21, F1 Inpari 13 x IRBB21 and DCF1 Ciherang resulted significant in weight of empty grain while DCF1 Inpari 13 resulted no significance in all of observed characters.Â Keywords: Rice, F1 Population, DCF1 Population, molecular marker, Xa geneÂ